Bone regeneration with recombinant human bone morphogenetic protein 2: a systematic review - Fernandes, Jannice de Queiroz; Lima, Valthierre Nunes de [UNESP]; Bonardi, Joao Paulo [UNESP]; Magro Filho, Osvaldo [UNESP]; Fernandes Queiroz, Sormani Bento (Springer, 2018)
Aim The aim of this work was to perform a systematic literature review on the clinical application of rhBMP-2 in bone reconstruction prior to placing implants. Materials and Methods A PUBMED search was made about the subject and nine clinical trials were selected according to strict inclusion criteria. Results Overall success rates of bone regeneration with rhBMP-2 was 81.4% and success of implants placed was 87.4%. Most frequent adverse events were pain, edema and erythema. Conclusion It was concluded that the treatment with rhBMP-2 foi satisfactory in most cases and the placement of dental implants in the bone regenerated with rhBMP-2 is feasible.
Keywords: Bone morphogenetic protein 2; Bone graft; Dental implants; Rehabilitation